Direct observation of precipitation along twin boundaries and dissolution in a magnesium alloy annealing at high temperature. (September 2017) - Guan, Dikai; Nutter, John; Sharp, Joanne; Gao, Junheng; Mark Rainforth, W.
Graphical abstract: Abstract: Precipitation along twin boundaries and dissolution in a cold-rolled Mg-Y-Nd alloy was directly observed for the first time during annealing at 490 °C. Precipitation occurred concurrently with recrystallization and the combined effect of precipitation and solute segregated to twin boundaries modified the recrystallization behaviour. Precipitates later dissolved into the matrix at the point where full recrystallization was nearly complete. The precipitates and higher solute concentration along original twin boundaries hindered grain growth of newly formed recrystallized grains. Even where twin boundaries had been consumed by recrystallization, the size of recrystallized grains were still controlled by the pre-existing twin boundaries.